Telling a national narrative that is not your own. Does it enable critical historical consumption?. (December 2014) - Lopez, Cesar; Carretero, Mario; Rodriguez-Moneo, Maria
National narratives are a key element in the process of history consumption and production. These master narratives have been analyzed in both theoretical and empirical studies as general schematic templates producing an essentialist and nationalist representation of the own past. The majority of studies examining historical representations of national narratives have used historical content of the students' own nation. This study, on the other hand, analyzed the historical understanding of 34 Spanish university students concerning three dimensions of historical narratives about a nation other than their own. These dimensions were: the establishment of the historical subject, the moral judgment about the national group actions, and the legitimacy of the ownership of the territory. The distinction among three different dimensions is presented as providing a better both theoretical and empirical comprehension of master narratives as sociocultural devices. Our results indicated that participants had a more critical representation about the second and third mentioned features, whereas they had a romantic conception about the first one, suggesting then that the establishment of the historical subject could be the core dimension of the master narrative. Finally, some considerations about the process of history consumption and its relations to national identity are presented.